Achieving High‐Performance Ternary Organic Solar Cells through Tuning Acceptor Alloy. Issue 6 (5th December 2016) - Chen, Yusheng; Ye, Pan; Zhu, Zhen‐Gang; Wang, Xinlong; Yang, Lei; Xu, Xiaozhou; Wu, Xiaoxi; Dong, Tao; Zhang, Hao; Hou, Jianhui; Liu, Feng; Huang, Hui
Abstract : Acceptor alloys based on n‐type small molecular and fullerene derivatives are used to fabricate the ternary solar cell. The highest performance of optimized ternary device is 10.4%, which is the highest efficiency for one donor/two acceptors‐based ternary systems. Three important parameters, J SC, V OC, and FF, of the optimized ternary device are all higher than the binary reference devices.